Mobilization of systemic CCL4 following HIV pre-exposure prophylaxis in young men in Africa - Petkov, Stefan; Herrera, Carolina; Else, Laura; Mugaba, Susan; Namubiru, Patricia; Odoch, Geoffrey; Opoka, Daniel; Pillay, Azure-Dee A. P.; Seiphetlo, Thabiso B.; Serwanga, Jennifer; Ssemata, Andrew S.; Kaleebu, Pontiano; et al. (Frontiers in Immunology, 2022)
HIV-1 pre-exposure prophylaxis (PrEP) relies on inhibition of HIV-1 replication steps. To understand how PrEP modulates the immunological environment, we derived the plasma proteomic profile of men receiving emtricitabine-tenofovir (FTC-TDF) or emtricitabine-tenofovir alafenamide (FTC-TAF) during the CHAPS trial in South Africa and Uganda (NCT03986970). The CHAPS trial randomized 144 participants to one control and 8 PrEP arms, differing by drug type, number of PrEP doses and timing from final PrEP dose to sampling. Blood was collected pre- and post-PrEP. The inflammatory profile of plasma samples was analyzed using Olink (N=92 proteins) and Luminex (N=33) and associated with plasma drug concentrations using mass spectrometry. The proteins whose levels changed most significantly from pre- to post-PrEP were CCL4, CCL3 and TNF-a; CCL4 was the key discriminator between pre- and post-PrEP samples. CCL4 and CCL3 levels were significantly increased in post-PrEP samples compared to control specimens. CCL4 was significantly correlated with FTC drug levels in plasma. Production of inflammatory chemokines CCL4 and CCL3 in response to short-term PrEP indicates the mobilization of ligands which potentially block virus attachment to CCR5 HIV-1 co-receptor. The significant correlation between CCL4 and FTC levels suggests that CCL4 increase is modulated as an inflammatory response to PrEP.